2021
DOI: 10.1111/jdv.17313
|View full text |Cite
|
Sign up to set email alerts
|

Flat scalp melanoma dermoscopic and reflectance confocal microscopy features correspond to histopathologic type and lesion location

Abstract: Background Dermoscopy and Reflectance Confocal Microscopy (RCM) features of scalp melanoma according to lesion location and histopathology have not been fully investigated.Objectives To reveal dermoscopic and RCM features of scalp melanoma according to lesion location and histopathology. MethodsWe retrospectively retrieved images of suspicious, atypical excised, flat melanocytic lesions of the scalp, assessed on dermoscopy and RCM at five centres, from June 2007 to April 2020. Lesions were classified according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…A study by Garbarino et al [22] more recently analysed the dermoscopic features of 97 scalp melanomas, including 64 LM. A high prevalence of features associated with both facial and extrafacial skin “architecture,” such as irregular pigment network (34.4%), irregular pseudo-network (59.4%), rhomboidal structures (37.5%), and annular-granular pattern (57.8%) was reported, similarly to our study.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Garbarino et al [22] more recently analysed the dermoscopic features of 97 scalp melanomas, including 64 LM. A high prevalence of features associated with both facial and extrafacial skin “architecture,” such as irregular pigment network (34.4%), irregular pseudo-network (59.4%), rhomboidal structures (37.5%), and annular-granular pattern (57.8%) was reported, similarly to our study.…”
Section: Discussionmentioning
confidence: 99%
“…In the Stanganelli et al 24 publication, the authors did not find a correlation between androgenetic alopecia and Breslow thickness, while Benati et al 33 found thicker melanomas in bald patients than in those with hair. Garbarino et al 49 analyzed 97 flat SMs and found that superficial spreading melanoma was most often invasive while the LM subtype was most often in situ. The authors hypothesized that LM demonstrates slower growth and easier diagnosis because it is visible to clinical examination 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Garbarino et al 49 analyzed 97 flat SMs and found that superficial spreading melanoma was most often invasive while the LM subtype was most often in situ. The authors hypothesized that LM demonstrates slower growth and easier diagnosis because it is visible to clinical examination 49 . In our study, melanomas in patients with androgenetic alopecia and elastosis were associated with lower Breslow thickness.…”
Section: Discussionmentioning
confidence: 99%
“…vascular pattern, irregular streaks, irregular pigmentation, irregular dots and globules and regression structures. [25][26][27] Nodular melanoma on the scalp may be either pigmented or amelanotic and is mostly thick/invasive and frequently demonstrates an unspecific pattern. For Recently, the blueblack (BB) rule has been introduced to increase dermoscopic diagnostic accuracy of pigmented NM (Figure 2).…”
Section: Key-pointsmentioning
confidence: 99%
“…In detail, early disease (LM) and more advanced disease (LMM) are associated with atypical pseudonetwork with increasing hyperpigmentation and obscuration of follicular openings as the lesions' Breslow thickness increases. Additionally, LM may display any of the well‐known dermoscopic melanoma features summarized in the 7‐point checklist, including atypical network, blue‐white veil, atypical vascular pattern, irregular streaks, irregular pigmentation, irregular dots and globules and regression structures 25–27 …”
Section: Melanoma On the Scalpmentioning
confidence: 99%